The sound diffusion in Italian Opera Houses: Some examples. Issue 4 (December 2020) - Tronchin, Lamberto; Merli, Francesca; Manfren, Massimiliano; Nastasi, Benedetto
Soundfield diffuseness in rooms is considered a fundamental aspect of a high-quality room acoustics. Since early studies by Hodgson up to more recent studies of Shtrepi and Embrechts, it was shown that high levels of sound diffuseness could guarantee blending of music, as well as spatial sound perception by listeners, and this could enhance the global indoor acoustic quality. Conversely, Italian-style Opera houses represent an important architectural place, in which the special features of the rich decorations, and the specific characteristics of the volume, give a unique atmosphere, including a peculiar psycho-acoustics impression. However, some geometric properties of the opera houses could influence the global acoustic perception. The shape of the marmorino wall on the stalls, as well as the parallelism of the lateral walls in the boxes, often causes a lack of spaciousness and sometimes in the worst cases provokes focalization. This phenomenon leads to design special devices that could be inserted in the theatres, to avoid focalization, even if they are rarely accepted. This article deals with the design of some acoustic diffusing panels and their functioning in three different theatres, combining both acoustics needs with architectural constraints. The article starts analysing and commenting on the issues that resulted from the measurements conducted in an Italian opera house. In the following step, three examples of the design of diffusing panels are proposed. Finally, the results of diffusion and scattering coefficient of panels realized in the last theatre considered here are reported.